PENGARUH KONFLIK PERAN GANDA DAN JOB STRESS TERHADAP KINERJA PERAWAT (STUDI PADA RUMAH SAKIT DI KOTA METRO) - Ardiansyah Japlani; Suwarto Suwarto; Karnila Ali (Jurnal Fokus Manajemen Bisnis, 2020)
The objective of this research is to determine the effect of family work conflict, work family conflict and job stress in influencing the nurse job performance in hospital, as well as to determine whether family work conflict, work family conflict variables can be influenced by job stress in nurse performance in hospital. The results of this study are expected to be used as a consideration for the hospital in evaluating the level of service to patients. This research is a quantitative causal research that allows to know the relationship that is influential between two or more variables by using SEM (Structural Equation Modeling). The population in this research is all female nurse who work at hospital in Metro (Muhammadiyah Hospital, Ahmad Yani Hospital, Mardiwaluyo Hospital, Islamic Hospital), while the study sample was 120 respondents with a non probability sampling purposive sampling method as a sampling method. Based on the results of the study that family work conflict has no positive effect on job stress. And also work family conflict has positive effect on job. Job stress has positive effect on job performance. In this study also shows that family work conflict has a negative effect on job performance. Work family conflict are also has postive effect on job performance. The implication of this research is that conflict of commitment and responsibility towards family is a key value in work family conflict. Recommendations in this reseacrh is for the hospitals to hold employee recreation activities with their families, it means that hospital get to know the families of the employees in order to tight the bonds between employees and their families